Beispiel Nr: 03
$ \text{Gegeben:}\\ \text{Kathete} \qquad a \qquad [m] \\ \text{Kathete} \qquad b \qquad [m] \\ \\ \text{Gesucht:} \\\text{Hypotenuse} \qquad c \qquad [m] \\ \\ c =\sqrt{a^{2} + b^{2} }\\ \textbf{Gegeben:} \\ a=5m \qquad b=12m \qquad \\ \\ \textbf{Rechnung:} \\ c =\sqrt{a^{2} + b^{2} } \\ a=5m\\ b=12m\\ c =\sqrt{(5m)^{2} + (12m)^{2} }\\\\c=13m \\ \small \begin{array}{|l|} \hline a=\\ \hline 5 m \\ \hline 50 dm \\ \hline 500 cm \\ \hline 5\cdot 10^{3} mm \\ \hline 5\cdot 10^{6} \mu m \\ \hline 0,005 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 12 m \\ \hline 120 dm \\ \hline 1,2\cdot 10^{3} cm \\ \hline 1,2\cdot 10^{4} mm \\ \hline 1,2\cdot 10^{7} \mu m \\ \hline 0,012 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline c=\\ \hline 13 m \\ \hline 130 dm \\ \hline 1,3\cdot 10^{3} cm \\ \hline 1,3\cdot 10^{4} mm \\ \hline 1,3\cdot 10^{7} \mu m \\ \hline 0,013 km \\ \hline \end{array}\\$